History of the National Academies of Sciences, Engineering, and Medicine's Institute for Laboratory Animal Research. (11th December 2022) - Kinter, Lewis B; Dysko, Robert C; Natterson-Horowitz, Barbara; Brayton, Cory F
Abstract: The Institute for Laboratory Animal Research (ILAR) was created within the National Academies of Sciences, Engineering, and Medicine (National Academies) in 1953 when biomedical research using animals was in its infancy in terms of quantity, quality, complexity, sophistication, and care. Over the intervening 69 years, ILAR has witnessed unprecedented growth, followed by unprecedented decline, and then regrowth in usage of specific species and models and an overall shift in experimental burden away from larger to smaller species (ie, mice, fish, and rats). ILAR has contributed much to the evolution of necessary research using animals and animal models for the benefit of humans, animals, and the environment and to the development and implementation of humane principles and standards for care and use of research animals. ILAR has served as a "neutral broker" seeking consensus, solutions, common ground, and pathways forward for all professional constituencies engaged in conduct of animal research. In 2022, ILAR will become the Board on Animal Health Sciences, Conservation, and Research (BAHSCR) within the Division on Earth and Life Studies of the National Academies and the ILAR Journal will pause publication with volume 62. This manuscript recounts the history and accomplishments of ILAR 1953–2022, emphasizing the past 2 decades. The manuscript draws upon ILAR's communications and previously published histories to document ILAR's leaders, reports, publications, conferences, workshops, and roundtables using text, tables, references, and extensive supplemental tables. The authors' intention is to provide the scientific community with a single source document for ILAR, and they apologize for any omissions and errors.